2019
DOI: 10.1016/j.fochx.2019.100027
|View full text |Cite
|
Sign up to set email alerts
|

Quality of lettuce Lactuca sativa (var. Tropicana M1) grown with two low-salinity shrimp effluents

Abstract: Highlights Control lettuce showed higher levels of proline than lettuce from other treatments. Well water lettuce exhibited higher levels of phenols than that from other treatments. Lettuce with low-salinity shrimp effluent exhibit a quality comparable to the control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Salinity stress has also been proven to negatively affect plant physiological and biochemical processes that in turn influence both primary and secondary metabolism of plants . Numerous studies have shown the negative effect of increasing levels of sodium chloride (NaCl) on plant height and vigor, on leaf area and on leaf number . Plant photosynthetic rate is also negatively affected by high salinity, which could change positively or negatively the protein content, thus affecting quality and inducing several plant secondary metabolism processes and antioxidant mechanisms to resist the impacts of salinity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity stress has also been proven to negatively affect plant physiological and biochemical processes that in turn influence both primary and secondary metabolism of plants . Numerous studies have shown the negative effect of increasing levels of sodium chloride (NaCl) on plant height and vigor, on leaf area and on leaf number . Plant photosynthetic rate is also negatively affected by high salinity, which could change positively or negatively the protein content, thus affecting quality and inducing several plant secondary metabolism processes and antioxidant mechanisms to resist the impacts of salinity .…”
Section: Introductionmentioning
confidence: 99%
“…6 Numerous studies have shown the negative effect of increasing levels of sodium chloride (NaCl) on plant height and vigor, 7-9 on leaf area 10,11 and on leaf number. 12,13 Plant photosynthetic rate is also negatively affected by high salinity, 14 which could change positively or negatively the protein content, 15 thus affecting quality and inducing several plant secondary metabolism processes 16 and antioxidant mechanisms to resist the impacts of salinity. 17,18 Several means for the alleviation of negative impacts of salinity have been suggested, including the exogenous application of cations, either through the rooting system or via foliar applications.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium toxicity disturbs the plant physiology by producing reactive oxygen species (ROS) and causes changes in the absorption of mineral elements. Concurrently, the accumulation of excess intracellular sodium ions affects the bioenergetic processes of photosynthesis, causing peroxidation of membranes and increasing the flavonoid content to fight the oxidative stress caused by salinity (MASTALERCZUK et al, 2019;RAMOS-SOTELO et al, 2019;DIN et al, 2020). Berilli et al (2015) reported chromium accumulation in conilon coffee seedlings using tannery sludge in solid phase as substrate, while Sales et al (2018b) found an increase in the flavonoid index in Schinus terebinthifolia seedlings grown in substrates with tannery sludge.…”
Section: Resultsmentioning
confidence: 99%
“…Since the quality of the harvested products is a very important factor for commercialization, a complementary study was carried out on the quality of the Tropicana M1 variety lettuce in all treatments (Ramos‐Sotelo et al . 2019). Lettuces cultivated in groundwater treatment presented higher concentrations of functional properties (phenolics, flavonoids and antioxidant capacity).…”
Section: State Of the Art Of Integrated Shrimp–plant Culturesmentioning
confidence: 99%